Facial muscle reanimation by transcutaneous electrical stimulation for peripheral facial nerve palsy. (3rd April 2019) - Mäkelä, Eeva; Venesvirta, Hanna; Ilves, Mirja; Lylykangas, Jani; Rantanen, Ville; Ylä-Kotola, Tuija; Suominen, Sinikka; Vehkaoja, Antti; Verho, Jarmo; Lekkala, Jukka; Surakka, Veikko; Rautiainen, Markus
Abstract: Reanimation of paralysed facial muscles by electrical stimulation has been studied extensively in animal models, but human studies in this field are largely lacking. Twenty-four subjects with a peripheral facial nerve palsy with a median duration of three years were enrolled. We studied activations of four facial muscles with electrical stimulation using surface electrodes. In subjects whose voluntary movement was severely impaired or completely absent, the electrical stimulation produced a movement that was greater in amplitude compared with the voluntary effort in 10 out of 18 subjects in the frontalis muscle, in 5 out of 14 subjects in the zygomaticus major muscle, and in 3 out of 8 subjects in the orbicularis oris muscle. The electrical stimulation produced a stronger blink in 8 subjects out of 22 compared with their spontaneous blinks. The stimulation could produce a better movement even in cases where the muscles were clinically completely paretic, sometimes also in palsies that were several years old, provided that the muscle was not totally denervated. Restoring the function of paralysed facial muscles by electrical stimulation has potential as a therapeutic option in cases where the muscle is clinically paretic but has reinnervation.